The Alternative of Drainage Construction Technology Selection by Using Analytical Hierarchy Process Method - Hafnidar A Rani; Tamalkhani Syammaun; Aulina Adamy; Ari Fadillah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Abstract: The drainage channel is one of the complementary buildings on the road segment in requiring one of the technical requirements for road infrastructure. The road drainage channels in general are open channels using gravity to drain surface water or inundation to the channel. The distribution of flow in the drainage channel to this channel follows the contours of the highway so that the water will flow easily following gravity. The Several alternatives selection of drainage development technologies include elbow drainage, parallel, grid iron, natural and radial. The problem found that some factor considered in selection the right technology are the construction budget, construction period, material supply, and construction process affecting the selection process become complicated. The purpose of this study is to determine the dominant criteria required in considering the selection of drainage construction technology in Banda Aceh and to determine the proper alternative using Analytical Hierarchy Process (AHP) method. After distributing questionnaires to 16 respondents, the research found that the dominant criterion is the construction period as the score of 0.66. According to the respondents, the construction period become the most vital criteria since the assessment of criteria variable relate to the limitation in complete all drainage proposed. This study founds that the best alternative in selecting drainage construction technology is